Influential Factors in the College Decision-Making Process for Chinese Students Studying in the U.S. - Rafi, Madeline A. (Journal of International Students, 2018)
For more than 1,043,839 international students, the United States is the destination of choice to pursue higher education. Although Chinese students account for almost one in three international students in the U.S., there are many unknowns about the influential factors behind their college decision. This qualitative study explores the self-described most important factors for Chinese students’ decision to attend college in the U.S. and the sources they seek to make their decision. This study found (1) parents are the most influential factor in the decision to attend college in the U.S., (2) students place great importance on rankings, and (3) in hindsight, students wish they focused less on rankings and did not need help from agencies when applying to colleges.